Peran Dinas Perhubungan Dalam Mengevaluasi Standar Keselamatan Penumpang Perahu Tambangan Tulungagung - Pertiwi, Amara Lintang; Satriya, Bambang; Ariyanti, Ariyanti (Bhirawa Law Journal, 2024)
The Department of Transportation is a government agency that has roles, obligations and responsibilities for the management and development of various aspects of the transportation system in an area both at the central and regional levels. The Department of Transportation is required to ensure compliance with applicable transportation safety standards, this is because the Department of Transportation is the main stakeholder in mobility management. Transportation plays a crucial role in moving people and goods from one location to another. Passenger protection is a key focus in the context of transportation security, to ensure the safety and comfort of passengers during travel. Evaluation of applicable security regulations and the role of the government in encouraging passenger protection reform is an important discussion. This study aims to determine the role and obstacles faced by the Tulungagung Regency Transportation Office in evaluating the safety standards of ferry boat passengers who have not obtained an operational permit. The research method used is Yuridical-Empirical, by conducting observations and interviews with the Head of Transportation and Facilities of the Tulungagung Regency Transportation Office. The results of this study found that the Transportation Department provides maximum efforts in providing supervision, protection, and socialization, but there are some unscrupulous service providers who do not comply with the procedures and rules that have been determined.